2023
DOI: 10.3390/cancers15071937
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Bacillus of Calmette-Guérin (BCG) Strains on Recurrence Rates among Intermediate/High-Risk Non-Muscle Invasive Bladder Cancers (NMIBCs): Single-Arm Study Systematic Review, Cumulative and Network Meta-Analysis

Abstract: Background: In an era of Bacillus of Calmette-Guérin (BCG) shortages, the comparative efficacy from different adjuvant intravesical BCG strains in non-muscle invasive bladder cancer (NMIBC) has not been clearly elucidated. We aim to compare, through a systematic review and meta-analysis, the cumulative BC recurrence rates and the best efficacy profile of worldwide available BCG strains over the last forty years. Methods: PubMed, Scopus, Web of Science, Embase, and Cochrane databases were searched from 1982 up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Connaught, Tice, and RIVM) are also resistant to cycloserine. Depending on the exact BCG strain, some patients benefit from additional, though less common, use of fluoroquinolones (like ofloxacin, ciprofloxacin, moxifloxacin, and levofloxacin) [26] . The use of corticosteroids within antimycobacterial treatment in patients with disseminated BCG infection highlights its presumptive underlying pathogenetic etiology of both hypersensitivity reaction and active infection.…”
Section: Discussionmentioning
confidence: 99%
“…Connaught, Tice, and RIVM) are also resistant to cycloserine. Depending on the exact BCG strain, some patients benefit from additional, though less common, use of fluoroquinolones (like ofloxacin, ciprofloxacin, moxifloxacin, and levofloxacin) [26] . The use of corticosteroids within antimycobacterial treatment in patients with disseminated BCG infection highlights its presumptive underlying pathogenetic etiology of both hypersensitivity reaction and active infection.…”
Section: Discussionmentioning
confidence: 99%
“…There are various strains of BCG in the world, such as TICE, RIVM, Connaught and Tokyo 172 et cetera. Studies have demonstrated varying e cacies among these different strains [11][12][13] . As for the side effects, there were no signi cant variations observed due to different doses of BCG nor were there any differences noted based on the varying brands of BCG 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…There are various strains of BCG in the world, such as TICE, RIVM, Connaught and Tokyo 172 et cetera. Studies have demonstrated varying e cacies among these different strains [11][12][13] . As for the side effects, there were no signi cant variations observed due to different doses of BCG nor were there any differences noted based on the varying brands of BCG 14,15 .Because of the prevalence of BC, Connaught strain (ImmuCyst) had been widely utilized to treat NMIBC.Nonetheless, there was a worldwide shortage of Connaught strain so that we have to introduce TICE strain (Oncotice) in our institution.…”
mentioning
confidence: 99%
“…Clinical trials have shown that BCG is safe and effective in reducing tumor recurrence and progression (104-109). Multiple BCG strains are available, which are considered to have equivalent efficacy and safety (11,17,(110)(111)(112).…”
Section: Intravesical Bcgmentioning
confidence: 99%